Pengaruh Intensitas Bermain Judi Online Terhadap Etika Keuangan Syariah Remaja Di Kecamatan Soreang - Fithriyyah Ridwan; St Nurhayati; Ririn Auliah Ridwan; Dhela Rahmatullah; Azizah Nurul Aliyah; Sangrina Sangrina (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This study examines the effect of online gambling intensity on the Islamic financial ethics of adolescents in Soreang District. The increasing accessibility of digital platforms has made online gambling more common among teenagers, raising concerns about its impact on financial behavior and moral values from an Islamic perspective. This research uses a quantitative approach with data collected through questionnaires distributed to 60 adolescent respondents. The data were analyzed using SPSS through validity and reliability tests, normality testing, correlation analysis, simple linear regression, and hypothesis testing. The results show that the intensity of online gambling has a negative and significant effect on adolescents’ Islamic financial ethics. This is indicated by a significance value of 0.000, a t-value of -7.85, and a correlation coefficient of -0.693, which reflects a strong negative relationship. In addition, the coefficient of determination shows that 48% of the variation in Islamic financial ethics is influenced by online gambling intensity, while the remaining 52% is affected by other factors outside the study. These findings suggest that the higher the intensity of online gambling, the lower the level of Islamic financial ethics among adolescents. Therefore, efforts to improve Islamic financial literacy, strengthen parental supervision, and increase government attention are necessary to reduce the negative effects of online gambling among youth.